Extracting structural information from MEH-PPV optical spectra - Milward, J; Marcus, M; Köhler, A; Barford, W (AIP Publishing, 2018)
The Frenkel-Holstein model in the Born-Oppenheimer regime is used to interpret temperature-dependent photoluminescence spectra of solutions made with the poly(p-phenylene vinylene) derivative MEH-PPV. Using our recently developed structural optimization method and assuming only intrachain electronic coupling, we predict the structure of emissive MEH-PPV chromophores in terms of a mean torsional angle ϕ0 and its static fluctuations σϕ, assuming no cis-trans defects. This allows us to fully account for the observed changes in spectra, and the chromophore structures obtained are consistent with the known phase transition at 180 K between a “red” and “blue” phase.